Out‐of‐pocket costs associated with head and neck cancer treatment. Issue 7 (24th August 2021) - Khan, Mohemmed N.; Hueniken, Katrina; Manojlovic‐Kolarski, Mirko; Eng, Lawson; Mirshams, Maryam; Khan, Khaleeq; Simpson, Colleen; Au, Michael; Liu, Geoffrey; Xu, Wei; Longo, Christopher J.; Goldstein, David P.; et al.
Abstract: Background: Out‐of‐pocket costs (OOPC) associated with treatment have significant implications on quality of life and survival in cancer patients. Head and neck cancer patients face unique treatment‐related challenges, but to date OOPC have been understudied in this population. Aims: This study aims to identify and measure OOPC for patients with head and neck cancer (HNC) in Ontario. Methods: HNC patients between 2015 and 2018 at Princess Margaret Cancer Centre in Toronto were recruited. Participants completed OOPC questionnaires and lost income questions during radiation, post‐surgery, and 3, 6, 12, and 24 months after completion of treatment. Associations between OOPC and treatment modality and disease site were tested with multivariable hurdle regression. Results: A total of 1545 questionnaires were completed by 657 patients. Median estimated OOPC for the total duration of treatment for participants undergoing chemoradiation was 1452 [0–14 616], for surgery with adjuvant radiation or chemoradiation (C/RT) was 1626, for radiation therapy alone was 635, and for surgery alone was 360. The major expenses for participants at the mid‐treatment time‐point was travel (mean 424, standard error of the mean [SEM] 34) and meals, parking, and accommodations (mean 617, SEM 67). In multivariable analysis, chemoradiation, surgery with C/RT, and radiation were associated with significantly higher OOPC than surgery alone during treatment (791% higher, p < .001; 539% higher, p < .001; 370% higher, p < .001 respectively) among patients with non‐zero OOPC. Participants with non‐zero OOPC in the laryngeal cancer group paid 49% lower OOPC than those with oropharyngeal cancers in adjusted analysis ( p = .025). Conclusions: Patients undergoing treatment for HNC pay significant OOPC. These costs are highest during treatment and gradually decrease over time. OOPC vary by patient demographics, clinical factors, and, in particular, treatment modality.